Geochemical characteristics and genesis of natural gas in the Yan'an gas field, Ordos Basin, China. (December 2016) - Feng, Ziqi; Liu, Dan; Huang, Shipeng; Gong, Deyu; Peng, Weilong
Highlights: First data on composition and isotopic analyses of the gases from Yan'an, Ordos Basin. Gases with > 95% methane were generated primarily from a humic source. Carbon isotope reversals result from secondary reactions at high maturity. Abstract: The Yan'an gas field in the Ordos Basin, China, was discovered in 2014 and contains reserves of up to 100 billion m 3 . Its occurrence in the basin contradicts the distribution model of "gas in the north, oil in the south". Upper Paleozoic natural gas in the Yan'an area is dominated by methane, with an average dryness coefficient (C1 /C1–4, %) of 99.5% (δ 13 C1 = −30.8 to −27.5‰), with minor amounts of CO2 = 3.8%, N2 = 0.5%, and ethane (δ 13 C2 = −37.2 to −30.5‰) and traces of higher hydrocarbons. The gas is predominantly coal-derived originating from Carboniferous–Permian humic hydrocarbon source rocks and minor oil-type gas from sapropelic source rocks. The carbon isotope series includes reversals, with δ 13 C2 < δ 13 C1 and rare δ 13 C3 < δ 13 C2 < δ 13 C1 . The enriched δ 13 C1 value is a result of the extremely high thermal maturity, while the depleted δ 13 C2 value cannot be explained solely by the simple addition of oil-type gas. The complex carbon isotope reversals result from the combined effects of several secondary reactions under extremely high thermal maturity.